Karakteristik Ibu dan Anak Sebagai Prediktor Stunting - Palupi, Rini; Kusuma, Anggi; Puspitarini, Zenni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Stunting is a physical growth disorder in children with its characteristic that is short stature. Besides being characterized by short or stunted stature, stunting is also characterized by impaired brain development. Stunting cases in Indonesia are still high even though they have decreased. To reduce the genesis of stunting, it is necessary to know the factors that cause stunting. This research objective was to determine the factors causing stunting from the characteristics of the mother and child. This type of research is quantitative with a case-control research design. The population in this research were all mothers who had toddlers aged 12-59 months at the Public Health Center of Kedaton in Bandar Lampung City. The sample in this research was 43 mothers with toddlers aged 12-59 months. The results of this research found that only the factor of exclusive breastfeeding was associated with stunting. This research expected that the government, health care workers, and the community will collaborate to reduce stunting rates. One way is to increase exclusive breastfeeding.Stunting yang merupakan ganggungan pertumbuhan fisik pada anak dengan cirinya yaitu bertubuh pendek.Selain ditandai dengan bertubuh pendek atau kerdil, stunting juga ditandai dengan terganggunya perkembangan otak. Kasus stunting di Indonesia masih tinggi meskipun sudah mengalami penurunan.Demi menurunkan angka kejadian stunting perlunya mengetahui faktor penyebab stunting.  Penelitian ini ditujukan untuk mengetahui faktor penyebab stunting dilhat dari karakteristik ibu dan anak.  Jenis penelitian ini adalah kuantitatif dengan desain penelitian case control. Populasi dalam penelitian ini adalah semua ibu yang memiliki balita usia 12 – 59 bulan di Puskesmas Kedaton Kota Bandar Lampung . Sampel dalam penelitian ini berjumah 43 ibu dengan anak balita usia 12-59 bulan.  Hasil penelitian ini didapatkan bahwa hanya faktor pemberian asi ekslusif yang berhubungan dengan stunting. Penelitian ini mengaharapkan pemerintah, tenaga kesehatan dan masyarakat berkolaborasimenurunkan angka stunting. Salah satu caranya dengan meningkatkan pemberian ASI ekslusif.